Analysis of Teacher's Needs for the Contextual-Based Reaction Rate E-module Integrated with Islamic Values - Badiatul Masngudah; Nurfina Aznam (Universitas Negeri Yogyakarta, 2024)
E-modules as learning support function to facilitate students' understanding in order to obtain meaningful learning. This study aims to explore teachers' needs for contextual-based e-modules integrated with Islamic values in the reaction rate material. The method used is an exploratory survey with a semi-open questionnaire technique, then the results obtained are analyzed using content analysis. The results of the study showed that participants still had difficulty finding sources/media that integrate Islamic values in chemistry material, especially reaction rate material. This makes contextual-based e-modules integrated with Islamic values in reaction rate material important to be developed as chemistry learning media. This e-module can help participants in preparing learning media. Thus, it can be seen that overall it is still necessary to develop contextual-based e-modules integrated with Islamic values in reaction rate material.